ASSOCIATION BETWEEN FUNCTIONAL MOBILITY, FEAR OF FALLING, AND COGNITIVE PERFORMANCE IN PEOPLE WITH PARKINSON'S DISEASE - Herberts, Bruna Machado; Martins, Valéria Feijó; Ferreira, Anderson Marques; Müller, Vivian Torres; Fontoura, Lucas da Rocha de Oliveira; Fernandes, Fernando Matheus de Mello; Dupin, Ana Luma Fernandes; Inda, Augusto Rossa; Mota, Rafael Pereira da Silveira; Gonçalves, Andrea Kruger; Martinez, Flávia Gomes (Seven Editora, 2026)
The aim of this study was to analyze the association between functional mobility, fear of falling, and cognitive performance in individuals with Parkinson’s disease (PD), as well as to investigate the relationship of these variables with age. This was a cross-sectional study conducted with participants enrolled in programs for individuals with PD at the Center for Reference in Aging and Movement. Functional mobility was assessed using the Timed Up and Go test (TUG), fear of falling was evaluated using the Falls Efficacy Scale (FES), and cognitive performance was measured using the Montreal Cognitive Assessment (MoCA). Associations between variables were analyzed using Spearman or Pearson correlation coefficients, according to data distribution, adopting a significance level of p < 0.05. The results indicated a negative correlation between cognitive performance and TUG time (r = −0.378; p = 0.021), suggesting that better cognitive performance was associated with better functional mobility. A positive correlation was also observed between age and TUG time (r = 0.486; p = 0.001), indicating poorer functional performance with increasing age. No significant associations were observed between fear of falling and the other variables analyzed. These findings indicate that functional mobility in individuals with PD may be associated with cognitive performance and age.